Underworld, underground, underhistory. Towards a counterhistory of waste and wastelands - David Williams (Przestrzenie Teorii)
The article is a collage of texts concerning the phenomena of waste in context underworld, underground and underhistory. Starting from environmentalism, cultural studies, sociology and psychoanalysis, the author moves towards a wide array of contemporary art practices. ‘Garbage’, ‘trash’, ‘refuse’, ‘waste’ and ‘rubbish’ are presented as complex and ambivalent metaphorical terms employed to organize and legitimize the parts of life normally desired to be overlooked. Waste: the excessive remainder of production and consumption, detritus of that which is deemed ‘use-less’ in ‘progress’; the informe material that has been reappropriated and recycled in countless artworks since the collages of Cubism, Dada and Surrealism’s détournements of objets trouvés. The author goes deeper: in order to present a global consciousness, he introduces a spectrum of artists and art works concerned with waste’s constitutive presence in and implications for contemporary landscapes, both literal and cultural. His description includes land artists, environmental artists, activists and conceptualists, such as Alan Sonfist, Agnes Denes, Agnès Varda, Edward Burtynsky, Maurizio Cattelan, and Mierle Laderman Ukeles.